2022
DOI: 10.1007/s11356-022-19102-4
|View full text |Cite
|
Sign up to set email alerts
|

Industrial agglomeration and carbon neutrality in China: lessons and evidence

Abstract: How does the agglomeration economy affect carbon emissions? Does it hinder China's zero-carbon emissions and carbon neutral goals? This study explored the impact of industrial agglomeration on carbon emissions and spatial spillover effects by expanding the output density theoretical model of Ciccone & Hall. The main findings are as follows: (1) Industrial labor and technology agglomerations increase regional carbon emissions, while industrial output agglomeration reduces emissions in the immediate term. Indust… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…Analyzing the control variables, it was discerned that Foreign Direct Investment (FDI) actively aids in curbing haze pollution. Such a trend implies the potential positive repercussions of foreign investments, possibly due to the influx of advanced, eco-friendly technologies, consistent with the observations by Yang et al (2019) and Tang et al (2022). Conversely, both the industrial structure and population size were found to be positively correlated with heightened haze pollution, echoing the perspectives of Shao et al (2019) and Yang et al (2020a).…”
Section: Direct Implications Of Trade Openness On Haze Pollutionsupporting
confidence: 83%
“…Analyzing the control variables, it was discerned that Foreign Direct Investment (FDI) actively aids in curbing haze pollution. Such a trend implies the potential positive repercussions of foreign investments, possibly due to the influx of advanced, eco-friendly technologies, consistent with the observations by Yang et al (2019) and Tang et al (2022). Conversely, both the industrial structure and population size were found to be positively correlated with heightened haze pollution, echoing the perspectives of Shao et al (2019) and Yang et al (2020a).…”
Section: Direct Implications Of Trade Openness On Haze Pollutionsupporting
confidence: 83%
“…(2) Industrial structure (instr): The industrialization process promotes rapid economic development but also causes various types of environmental pollution. However, optimizing the industrial structure and promoting innovation-driven development of industries can effectively improve carbon productivity [58]. This paper selects the ratio of value added of the secondary industry and GDP in each region to measure the industrial structure.…”
Section: Control Variablesmentioning
confidence: 99%
“…Studies on carbon emissions from land use [14], carbon emissions from energy consumption [15], and embodied carbon emissions from trade [16] have also gradually increased. Regarding the influencing factors of carbon emissions, related research focuses on urbanization [17], technological innovation [18], energy consumption scale [19], and industrial agglomeration [20], these studies use the LMDI model [21], spatial econometric model [22] and threshold effect to conduct in-depth research. According to IPCC (2019) data, China's carbon emissions from manufacturing accounted for 53.27% of the country's total carbon emissions in 2017.…”
Section: Introductionmentioning
confidence: 99%